TREN GLOBAL RISET KEARIFAN LOKAL DAN PEMBANGUNAN BERKELANJUTAN: ANALISIS BIBLIOMETRIK BERBASIS VOSVIEWER TAHUN 2021-2025 - Ahmad Fadly; Martin Kustati; Bashori (PT. Sulthan Journal Publisher, 2025)
This study aims to map and analyze the development of global research on local wisdom within the context of sustainable development using a bibliometric approach. Research data were obtained from scientific publications published between 2021 and 2025 and analyzed using VOSviewer to identify collaboration patterns, thematic structures, and the dynamics of research topics. The analysis was conducted through co-occurrence, overlay, and density visualizations to reveal the relationships among keywords and temporal research trends. The findings indicate that local wisdom occupies a central position as a key node connecting various cross-disciplinary themes, particularly sustainability, indigenous knowledge, environmental management, climate change, and education. Overlay and heatmap visualizations demonstrate increasing publication intensity on contemporary themes, especially the integration of local wisdom with character education, project-based learning, and learning technologies such as augmented reality. These findings affirm a shift in research direction from descriptive–cultural approaches toward more applicative, interdisciplinary, and innovation-based perspectives. Overall, this study provides a comprehensive overview of the landscape and direction of global research development on local wisdom. It contributes to strengthening theoretical understanding while also offering a strategic foundation for the development of future research oriented toward character building, social resilience, and the achievement of sustainable development goals.